Transcatheter Mitral Valve Replacement and Thrombosis: A Review - Ascione, Guido; Denti, Paolo (Frontiers in Cardiovascular Medicine, 2021)
Mitral regurgitation is the most prevalent form of moderate or severe valve disease in developed countries. Surgery represents the standard of care for symptomatic patients with severe mitral regurgitation, but up to 50% of patients are denied surgery because of high surgical risk. In this context, different trans-catheter option have been developed to address this unmet need. Trans-catheter mitral valve replacement (TMVR) is an emergent field, representing an alternative option in high complex contexts, when trans-catheter mitral valve repair is not feasible or suboptimal due to anatomical issues. However, TMVR is burdened by some device-specific issues (device malposition, migration or embolization, left ventricular outflow tract obstruction, hemolysis, thrombosis, stroke). Here we discuss the thrombotic risk of TMVR and current evidence about anticoagulation therapy after TMVR.